How do people view price and wage inflation? - Monica Jain; Olena Kostyshyna; Xu Zhang (Bank of Canada, 2022)
This paper examines novel household-level data from the Canadian Survey of Consumer Expectations (CSCE) from 2014Q4 to 2022Q1 to understand households' expectations about price and wage inflation, their respective links to views about labour market conditions and their subsequent impact on households' outlook for real spending growth. We find, consistent with recent research, that households associate higher expected price inflation with worse labour market conditions. In contrast, higher expected wage growth is linked to better labour market outcomes-an avenue not previously explored-and consistent with standard macroeconomic models. These differing supply-side and demand-side views of price inflation and wage inflation are reflected in households' spending outlook: expected real spending is negatively linked to inflation expectations but positively linked to expected wage inflation. Finally, the link between households' inflation expectations and wage growth expectations is weak, suggesting limited pass-through from consumers' inflation expectations into their expected wage gains, and thus a lower likelihood of entering a wage-price spiral.
Keywords: E21; E24; E31; C83; D84; 330; Inflation and Prices; Monetary Policy Communications